A case series of imperforate hymen - Sakhifa, Sithi A.; Priyadharshini, Moneekha; Jayanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Imperforate hymen is an uncommon congenital anomaly of the female genital tract, which is caused by the persistence of the hymenal membrane to perforate during embryogenesis. Although it is benign, delayed diagnosis can cause marked morbidity and it typically occurs in adolescents with primary amenorrhea, cyclic abdominal pain, urinary retention, or pelvic mass. Their early recognition is essential to prevent patients from developing sequelae such as endometriosis, infection, infertility, or urinary tract injury. We report a series of three adolescent girls with imperforate hymen who presented with abdominal pain, urinary retention and primary amenorrhea. Diagnosis was based on physical examination, including ultrasonography and all patients were managed with hymenotomy or hymenectomy with good response and return of normal menstruation. This case series emphasizes the need for a high index of suspicion of imperforate hymen in adolescent girls with lower abdominal pain or delayed menarche and that timely diagnosis, correction, and surgical management are crucial to prevent long-term complications.